2002
DOI: 10.1038/sj.bjp.0704470
|View full text |Cite
|
Sign up to set email alerts
|

The role of β3‐adrenoceptors in mediating relaxation of porcine detrusor muscle

Abstract: 1 b-adrenoceptors mediate relaxation of bladder detrusor smooth muscle. This study investigates the contribution of b 3 -adrenoceptors to relaxation of the pig urinary bladder. 2 Cell membranes were prepared from detrusor muscle of the pig bladder dome and competition experiments with [ 3 H]-dihydroalprenolol (DHA), a non-selective b-adrenoceptor antagonist was used as a speci®c radioligand to determine the presence of b-adrenoceptor subtypes. In functional experiments, isolated detrusor muscle strips were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
4
51
1
Order By: Relevance
“…Previous studies have employed two different approaches to measure urinary bladder relaxation by ␤-adrenergic receptor agonists, i.e., relaxation against passive tension (Lecci et al, 1998;Yamazaki et al, 1998;Igawa et al, 1999) or relaxation against active tone, induced, e.g., by depolarizing concentrations of KCl (Oshita et al, 1997;Longhurst and Levendusky, 1999;Kobayashi et al, 2000;Yamanishi et al, 2002Yamanishi et al, , 2003. Since we hypothesized that the extracellular potassium concentration may affect the relative role of potassium channels, we have used both approaches in parallel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have employed two different approaches to measure urinary bladder relaxation by ␤-adrenergic receptor agonists, i.e., relaxation against passive tension (Lecci et al, 1998;Yamazaki et al, 1998;Igawa et al, 1999) or relaxation against active tone, induced, e.g., by depolarizing concentrations of KCl (Oshita et al, 1997;Longhurst and Levendusky, 1999;Kobayashi et al, 2000;Yamanishi et al, 2002Yamanishi et al, , 2003. Since we hypothesized that the extracellular potassium concentration may affect the relative role of potassium channels, we have used both approaches in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have failed to unequivocally identify the ␤-adrenergic receptor subtype mediating bladder relaxation in the rat, we have based our present study on isoproterenol, an agonist that similarly acts on all known ␤-adrenergic receptor subtypes (Hoffmann et al, 2004). Previous studies on bladder relaxation by ␤-adrenergic agonists have employed two different approaches: relaxation against passive tension (Lecci et al, 1998;Yamazaki et al, 1998;Igawa et al, 1999) or relaxation against active tone, induced, e.g., by depolarizing concentrations of KCl (Oshita et al, 1997;Longhurst and Levendusky, 1999;Kobayashi et al, 2000;Yamanishi et al, 2002). Since we expected this methodological difference to affect the relative role of potassium channels in bladder relaxation, all our experiments were performed under both conditions.…”
mentioning
confidence: 99%
“…␤ 2 -Adrenoceptor is the predominant subtype mediating the vascular smooth muscle-relaxant properties (32). ␤ 3 -Adrenoceptor was initially identified in adipose tissue, and its presence has been recently demonstrated in a variety of tissues including blood vessel (32), gastrointestinal tract (9), urinary bladder smooth muscle (43), and retinal endothelial cell (37). In the present study, our results have demonstrated that, in anesthetized, open-chest, and artificially ventilated rats, inhalation of epinephrine aerosol substantially enhanced pulmonary C-fiber responses to lung inflation and capsaicin injection (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that species differences exist in the distributions and roles of ␤-ARs in the bladder (for comprehensive review, see Michel and Vrydag, 2006). Bladder relaxation evoked by ␤-AR agonists is mediated mainly via ␤ 1 -ARs in cats (Nergardh et al, 1977) and guinea pigs (Li et al, 1992), by ␤ 2 -ARs in rabbits, by both ␤ 2 -and ␤ 3 -ARs in rats (Yamazaki et al, 1998) and pigs (Yamanishi et al, 2002), and by ␤ 3 -ARs in the ferrets (Takeda et al, 2000), dogs (Yamazaki et al, 1998), and primates (Takeda et al, 2002a). Based on mRNA expression, at least 95% of the adrenoceptor message in human bladder comprises the ␤ 3 -AR subtype (Nomiya and Yamaguchi, 2003).…”
Section: Gw427353 Evoked Relaxation That Was Attenuated By the Nonselmentioning
confidence: 99%